Metabolic checkpoints in the regulation of Th17 cells: implications for uveitis pathogenesis and therapy - Ma, YongFei; Zhang, QiuJin; Ding, ZhiXiang (Frontiers in Immunology, 2026)
The disruption of the balance between helper T cells (Th17) and regulatory T cells (Tregs) is associated with various autoimmune diseases. Th17 cells contribute to inflammation, whereas Tregs play a crucial role in suppressing autoimmunity. Th17 cells are central to the pathogenesis of autoimmune diseases, with specific metabolic pathways, enzymes, signaling pathways, and transcription factors acting as key checkpoints that influence T cell differentiation and immune responses. This review aims to summarize recent advances in understanding the role of Th17 cells and the Th17/Treg immune balance in the pathogenesis of uveitis, focusing on the impact of metabolic reprogramming on the activation, differentiation, and effector functions of T cells. Understanding the regulators of key metabolic checkpoints offers promising prospects for the treatment of autoimmune diseases, including Th17-mediated uveitis.